HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR MAHASISWA DALAM MENGERJAKAN SKRIPSI DI STIKES BINA SEHAT PPNI MOJOKERTO - Ratnaningsih, Tri; Astutik, Widya (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Anxiety is an individual response to a state that is not pleasant. Anxiety often disrupt sleep. A person whose mind is filled with personal problems and find it difficult to relax while going to start sleeping. It is mainly experienced by the student in completing the thesis. Feelings of anxiety experienced by students due to the search for literature, to determine the theme to be studied, fearing title consulted rejected by the supervisor, as well as difficulties in the process of preparation of the thesis. The research objective was to determine whether there is a correlation with the level of anxiety on sleep quality in a student high school thesis work in STIKES Bina Sehat PPNI Mojokerto. Correlational research design analytic case-control approach. The entire student population Nursing courses S1 final degree thesis that working at Bina Sehat STIKES PPNI Mojokerto much as 129 students obtained a sample of 56 students were taken to the accidental sampling. Data taken using a questionnaire Hars to levels of anxiety and PSQI questionnaire for sleep quality. After processing the collected data and performed statistical Test Spearman Rho continued Test with SPSS version 20.0. the results showed ρ (value) = 0.005 and α = 0.05 then ρ <α so that H0is rejected it means there is a correlation with sleep quality level of anxiety on students in doing thesis in STIKES Bina Sehat PPNI Mojokerto. The role of the supervisor who can actively influence the process of preparation of the thesis in order to run well and has a high spirit, perseverance in learning, have the tenacity and courage in doing thesis.Keywords:Anxiety Level, Sleep Quality, Students High School